2017
DOI: 10.4236/ajps.2017.810172
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of Ten-DPA Fiber in an Upland Cotton (<i>Gossypium hirsutum</i>) Line with Improved Fiber Traits from Phytochrome A1 RNAi Plants

Abstract: Silencing phytochrome A1 gene (PHYA1) by RNA interference in Upland cotton (Gossypium hirsutum L. cv. Coker 312) had generated PHYA1 RNAi lines with improved fiber quality (longer, stronger and finer fiber). To reveal molecular mechanisms that govern fiber development with positive fiber traits, a study of global gene expression profiling of 10-DPA fibers in a PHYA1 RNAi line and its parent Coker 312 was conducted by high-throughput RNA sequencing. A comparative analysis of transcriptomes between the two lines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 51 publications
(59 reference statements)
0
4
0
Order By: Relevance
“…The expression levels of most of the SOD genes were higher at 10 DPA than at 20 DPA (Figure 4A,B). The result showed that the SOD genes are integral at 10 DPA, being a critical stage of fiber initiation and elongation, moreover, at the stage of 10 DPA, ABA inhibits fiber cell initiation and elongation [33]. Moreover, previous studies have shown that cotton annexin proteins; AnxGh1:AAR13288, AnxGh2:AAB67993, AnxGhFx:FJ415173, and AnxGhF:AAC33305 are present in higher amount in fibers of 10 DPA wild-type plants as compared to the fuzzless-lintless mutant [34].…”
Section: Resultsmentioning
confidence: 99%
“…The expression levels of most of the SOD genes were higher at 10 DPA than at 20 DPA (Figure 4A,B). The result showed that the SOD genes are integral at 10 DPA, being a critical stage of fiber initiation and elongation, moreover, at the stage of 10 DPA, ABA inhibits fiber cell initiation and elongation [33]. Moreover, previous studies have shown that cotton annexin proteins; AnxGh1:AAR13288, AnxGh2:AAB67993, AnxGhFx:FJ415173, and AnxGhF:AAC33305 are present in higher amount in fibers of 10 DPA wild-type plants as compared to the fuzzless-lintless mutant [34].…”
Section: Resultsmentioning
confidence: 99%
“…PCR reaction and data collection were performed by using Applied Biosystems ® QuantStudio ® 3 (USA) with 2X SG Fast qPCR Master Mix (Low Rox) (Sangon Biotech, China). Relative gene expression levels were calculated by using the 2 -DDCT method with three replicates (Miao et al, 2017). All data were normalized against the expression level of the wheat actin gene.…”
Section: Real-time Pcr Analysismentioning
confidence: 99%
“…Predicted corresponding cotton genes are annotated on the basis of high similarity to the Arabidopsis orthologues. Transcripts of genes encoding extensin proteins have been identified in transcriptomics studies to be highly enriched both at 10 and 20 days post anthesis (DPA), further suggesting involvement in the fibre development ( Islam et al, 2016 , Miao et al, 2017 ). Also, in one of the three regression models a correlation between extensin content and fibre length and strength was indicated ( Rajasundaram et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%